Periglomerular afferent innervation of the mouse renal cortex - Tyshynsky, Roman; Sensarma, Sulagna; Riedl, Maureen; Bukowy, John; Schramm, Lawrence P.; Vulchanova, Lucy; Osborn, John W. (Frontiers in Neuroscience, 2023)
Recent studies using a novel method for targeted ablation of afferent renal nerves have demonstrated their importance in the development and maintenance of some animal models of hypertension. However, relatively little is known about the anatomy of renal afferent nerves distal to the renal pelvis. Here, we investigated the anatomical relationship between renal glomeruli and afferent axons identified based on transient receptor potential vanilloid 1 channel (TRPV1) lineage or calcitonin gene related peptide (CGRP) immunolabeling. Analysis of over 10,000 glomeruli from wildtype C57BL/6J mice and transgenic mice expressing tdTomato in TRPV1 lineage cells indicated that approximately half of all glomeruli sampled were closely apposed to tdTomato+ or CGRP+ afferent axons. Glomeruli were categorized as superficial, midcortical, or juxtamedullary based on their depth within the cortex. Juxtamedullary glomeruli were more likely to be closely apposed by afferent axon subtypes than more superficial glomeruli. High-resolution imaging of thick, cleared renal slices and subsequent distance transformations revealed that CGRP+ axons closely apposed to glomeruli were often found within 2 microns of nephrin+ labeling of glomerular podocytes. Furthermore, imaging of thick slices suggested that CGRP+ axon bundles can closely appose multiple glomeruli that share the same interlobular artery. Based on their expression of CGRP or tdTomato, prevalence near glomeruli, proximity to glomerular structures, and close apposition to multiple glomeruli within a module, we hypothesize that periglomerular afferent axons may function as mechanoreceptors monitoring glomerular pressure. These anatomical findings highlight the importance of further studies investigating the physiological role of periglomerular afferent axons in neural control of renal function in health and disease.